Peningkatan Kesadaran Hukum Masyarakat di Dusun Sanggrahan II, Desa Muntuk, Kecamatan Dlingo, Kabupaten Bantul, DIY - Dewi Nurul Musjtari; Maesyaroh Maesyaroh (Universitas Mathla'ul Anwar Banten, 2019)
THE IMPROVEMENT OF COMMUNITY LEGAL AWARENESS IN SANGGRAHAN II, MUNTUK VILLAGE, DLINGO SUB DISTRICT, BANTUL DISTRICT, DIY PROVINCE. The formulation of the problem in the community service activities is how is the process of increasing legal awareness for the community in Sanggrahan II, Muntuk Village, Dlingo Sub District, Bantul District, DIY Province. The method used is counseling, training, focus group discussion, and mentoring. The activity was carried out with the participation of administrators, the Family Welfare Program group and the community. The results of this community service activity were that the process of increasing legal awareness for the community in Sanggrahan II, Muntuk Village, Dlingo Sub-District, Bantul District, DIY Provine was carried out with 3 (three) types of activities including: legal Comuncation on the legal awareness (neighbors and familylLaw), training for facilitator of the legal awareness and mentoring in resolving disputes in the community of Sanggrahan II, Muntuk Village, Dlingo Sub District, Bantul District, DIY Province.